2011
DOI: 10.4081/hr.2011.e26
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Bcl-2 and Bcl-6 Immunostaining in B-Non Hodgkin's lymphoma

Abstract: The determination of prognosis for B-Non-Hodgkin's lymphoma (NHL) is known to be related to the multiple differences in tumor cell biology. Bcl-2 and Bcl-6 are two markers linked to germinal center B cells. Both markers are thought to have an effect on prognosis of mature B-cell neoplasms. Forty-four patients with chronic B-cell neoplasm were included; Bcl-2 and Bcl-6 expression by immunohistochemistry was examined. Bcl-2 protein was positive in 36.4% (16 of 44) of cases (62.5% of follicular lymphoma, 16.7% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…These two proteins are frequently found in B‐cell NHL, and both should be considered as reliable prognostic markers. Although some reports failed to show any impact of BCL2 protein expression on survival , subsequent studies have reported that BCL2‐positive cases have a worse prognosis , which is in line with the data presented herein for patients who underwent R‐B immunochemotherapy. Until now, published data regarding expression of BCL6 were conflicting because some authors observed a negative impact on the outcome of B‐cell lymphoma , whereas others did not .…”
Section: Discussionsupporting
confidence: 90%
“…These two proteins are frequently found in B‐cell NHL, and both should be considered as reliable prognostic markers. Although some reports failed to show any impact of BCL2 protein expression on survival , subsequent studies have reported that BCL2‐positive cases have a worse prognosis , which is in line with the data presented herein for patients who underwent R‐B immunochemotherapy. Until now, published data regarding expression of BCL6 were conflicting because some authors observed a negative impact on the outcome of B‐cell lymphoma , whereas others did not .…”
Section: Discussionsupporting
confidence: 90%
“…The tumor cells were robustly positive for CD20 and Bcl-2; however, they were negative for CD3, Bcl-6, CD10, MUM-1, and CMV. Bcl-6 and CD10 are usually positive in germinal center type DLBCL and Bcl-6 can be considered as a good prognostic marker, but our case was negative for these two markers [ 13 ]. MUM-1 is usually positive in activated B-cell type of DLBCL [ 14 ], but it was also negative in our case.…”
Section: Discussionmentioning
confidence: 96%
“…Faster progression of the tumor was reflected by high KI-67 proliferation index, but one good prognostic feature was the absence of BCL-2 staining, which helps in good chemotherapy and radiotherapy response as reported in different studies [ 9 ]. In the previous, reported cases mimicking meningioma BCL-2 staining in FISH were presented, suggesting a poor response to treatment [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 98%